Technostress and Psychological Well-Being Among Work-From-Anywhere (WFA) Workers in Kalimantan, Indonesia - Ramadhina, Novianti Rizky; Fauzia, Rahmi; Tanau, Meydisa Utami (Nusantara Journal of Behavioral and Social Science, 2026)
Work From Anywhere (WFA) arrangements expand geographic flexibility but intensify reliance on information and communication technologies, potentially increasing technostress and undermining psychological well-being. This cross-sectional study examined the association between technostress and psychological well-being among WFA workers in Kalimantan, Indonesia. Using purposive sampling, 171 eligible digital/ICT workers (20–45 years; ≥3 months WFA; >40 hours/week; excluding interns and freelancers) completed an online survey (February–March 2025) including the Technostress Creators Scale and Ryff’s Psychological Well-Being Scale (PWBS). Participants were predominantly female (55.6%) and worked mainly in IT and digital marketing roles. Assumption checks supported normality and linearity. Simple linear regression showed that technostress was significantly and negatively associated with psychological well-being (B = −0.873, SE = 0.092, β = −0.591, t = −9.628, p < .001). The model was significant, F(1, 169) = 92.70, and explained 34.9% of the variance in psychological well-being (R² = .349; adjusted R² = .346). These findings suggest that technology-related demands constitute a substantial correlate of well-being in WFA settings and highlight the need for organizational practices that reduce techno-overload and techno-invasion, strengthen digital support, and protect recovery time. Future research should test mechanisms (e.g., strain and detachment) and incorporate key covariates using longitudinal or diary designs.   Abstrak: Pengaturan kerja Work From Anywhere (WFA) memperluas fleksibilitas geografis, namun meningkatkan ketergantungan pada teknologi informasi dan komunikasi sehingga berpotensi meningkatkan technostress dan menurunkan kesejahteraan psikologis. Studi potong lintang ini menguji hubungan antara technostress dan kesejahteraan psikologis pada pekerja WFA di Kalimantan, Indonesia. Dengan teknik purposive sampling, sebanyak 171 pekerja digital/ICT yang memenuhi kriteria (usia 20–45 tahun; menjalani WFA ≥3 bulan; bekerja >40 jam/minggu; tidak termasuk magang dan pekerja lepas) mengisi survei daring (Februari–Maret 2025) yang mencakup Technostress Creators Scale dan Ryff’s Psychological Well-Being Scale (PWBS). Partisipan didominasi perempuan (55,6%) dan terutama bekerja pada bidang IT serta digital marketing. Pemeriksaan asumsi mendukung normalitas dan linearitas. Regresi linear sederhana menunjukkan bahwa technostress berasosiasi negatif dan signifikan dengan kesejahteraan psikologis (B = −0,873, SE = 0,092, β = −0,591, t = −9,628, p < 0,001). Model signifikan, F(1,169) = 92,70, dan menjelaskan 34,9% variasi kesejahteraan psikologis (R² = 0,349; adjusted R² = 0,346). Temuan ini menunjukkan bahwa tuntutan terkait teknologi merupakan korelat substansial bagi kesejahteraan dalam konteks WFA, serta menegaskan perlunya praktik organisasi untuk menurunkan techno-overload dan techno-invasion, memperkuat dukungan digital, dan melindungi waktu pemulihan. Riset selanjutnya perlu menguji mekanisme (mis. strain dan detachment) serta memasukkan kovariat kunci melalui desain longitudinal atau diary.